PENDIDIKAN DAN BUDAYA: PEMBENTUKAN KONSEP DIRI PESERTA DIDIK MINORITAS MELALUI KONSELING LINTAS BUDAYA - annisah fadila (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2020)
Indonesia is a country that has a diverse culture, each region has unique and distinctive cultural characteristics. Cultural differences in each region will affect students' self-concept. The concept of self is the individual's beliefs, views and judgments on him, self-concepts that are not genetic or inherited from parents but are determined by the results of interaction with the environment both parents and the surrounding environment. Self-concept has a very important role in determining student behavior and the future, therefore education is needed as an effort to form self-concept in students in order to develop optimally. Cross-cultural counseling is one of the efforts can be made in educational efforts to shape students' self-concept, where cross-cultural counseling has a role in helping the targeting process that is consistent with the client's life experience and cultural values, recognizing the client's identity to include individual dimensions, group and universal, supporting universal use, strategies and specific roles of culture in the healing process, and balancing the importance of individualism and collectivism.